(untitled) (Research, Society and Development, 2022)
Fetal alcohol syndrome (FAS) is a condition of malformations caused to the individual who was exposed to alcohol during pregnancy. The consumption of alcohol by women has been increasing, which includes the group of pregnant women, and consequently the number of children with anomalies increases. Therefore prevention is important, as FAS is totally preventable. It has a complex diagnosis, through facial features and the mother’s own report about alcohol consumption, in addition to specialized and individualized treatment. The aim of this study is to report the case of a 12-year-old male patient with a complaint of the absence of lower incisors. The same presented dental agenesis, in addition to ankyloglossia and buccofacial characteristics, which raise the diagnostic hypothesis of Fetal Alcohol Syndrome, describing through a literature review, which are the phenotypic aspects resulting from the syndrome, approaching the diagnosis which the treatment plan, the surgical steps of lingual frenectomy and dental follow-up recommended for the case.